DAMPAK PROFITABILITAS, LEVERAGE, DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP NILAI PERUSAHAAN LQ45 - Orfyanny S Themba; Muskilaturrahmi Muskilaturrahmi; Riska Auliah (STIE AMKOP, 2020)
Good company performance is an asset that must be met by companies in Indonesia in order to attract investors and make the company’s value. The variables used as a measure of firm value in this study are the level of profitability, Leverage, and Good Corporate Governance (GCG). The purpose of this study is to determine how far the influence of profitability, leverage and good corporate governance (GCG) affect firm value. The data was taken from LQ45 companies listed on the Indonesia Stock Exchange (IDX) in the 2018 period. A total of 45 LQ45 companies were used as samples. The result of this study are the coefficient of determination (R^2) which shows the profitability, leverage and GCG variables to be able to explain the fir value of 0,4%. Simultaneous test results or F test, namely f-count > f-table 97,620 > 2,2,833) with a significance of 0,000 has a meaning with an error rate og 5%. The t test result show that the profitability variable has a significant positive effect on the firm value variable. Leverage variable has negative effect on company variable and it is not significant. The GCG variable does not affect the firm value variable. Keywords : Good Corporate Governance, Leverage, Profitabilitas